Cover Feature: Tackling Capacity Fading in Vanadium Redox Flow Batteries with Amphoteric Polybenzimidazole/Nafion Bilayer Membranes (ChemSusChem 12/2019). Issue 12 (24th June 2019) - Oldenburg, Fabio J.; Nilsson, Elisabeth; Schmidt, Thomas J.; Gubler, Lorenz
Abstract : The Front Cover shows the mitigation of capacity fading in a vanadium redox flow battery through the use of a bilayer membrane consisting of a cation exchange membrane with a layer of polybenzimidazole having thickness in the micrometer range. More information can be found in the Full Paper by Oldenburg et al. on page 2620 in Issue 12, 2019 (DOI: 10.1002/cssc.201900546 ).